The Preventive Effects of Fermented and Germinated Foxtail Millet Whole Grain on Kidney Damage in a Diabetic Mouse Model - Liu, Xia; Qiu, Bin; Liu, Wei; Zhang, Yuhan; Wang, Xianshu; Li, Xingang; Li, Lingfei; Zhang, Di (Frontiers in Nutrition, 2022)
Diabetic kidney disease (DKD) is an important complication of diabetes. The prevention of DKD can effectively reduce the mortality rate of diabetic patients and improve their quality of life. The present study examined the effects of fermented and germinated foxtail millet whole grain (FG-FM) on kidney lesions in a diabetic mouse model (Db/Db mice). The results proved that the FG-FM consumption significantly alleviated the kidney tissue damage in the diabetic mouse model. The transcriptome analysis of kidney tissues demonstrated that the overactivation of signaling pathways related to inflammation and immunity in the diabetic mouse model was significantly inhibited with the FG-FM intake. Moreover, the consumption of the FG-FM diet effectively elevated the bacterial diversity, increased the relative abundance of probiotics and decreased the relative abundance of previously reported DKD-related bacteria in the gut microbiota of diabetic mice. Our study confirmed foxtail millet as a potential source of functional food for the non-pharmacological intervention of DKD.